2016
DOI: 10.1002/ejic.201600592
|View full text |Cite
|
Sign up to set email alerts
|

Aroylphosphanes: Base‐Free Synthesis and Their Coordination Chemistry with Platinum‐Group Metals

Abstract: Aroylphosphanes: base-free synthesis and their coordination chemistry with platinum-group metals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Saunders to the previous observation, a small increase in ν(CO) is observed upon coordination to metal centers in all cases. [30] Kumar et al presented the reaction between bidentate bis (acyl phosphine) ligands 20a and 20b with [Pd(η 3 -C 3 H 5 )Cl] 2 which leads to the formation of binuclear Pd (II) complex [Pd 2 (η 3 -C 3 H 5 ) 2 Cl 2 {1,3-{Ph 2 PC (O)} 2 (C 6 H 4 )}] (119) as depicted in Scheme 33. On the other hand, the reaction of ligand 20a with [Pd(COD)Cl 2 ] in the presence of AgClO 4 resulted in the formation of a PCP-type pincer complex, [PdCl{2,6-{Ph 2 PC(O)} 2 (C 6 H 3 )}] (120) via C-H bond activation in good yield.…”
Section: Group 7 Metal Chemistry (M = W)mentioning
confidence: 99%
See 2 more Smart Citations
“…Saunders to the previous observation, a small increase in ν(CO) is observed upon coordination to metal centers in all cases. [30] Kumar et al presented the reaction between bidentate bis (acyl phosphine) ligands 20a and 20b with [Pd(η 3 -C 3 H 5 )Cl] 2 which leads to the formation of binuclear Pd (II) complex [Pd 2 (η 3 -C 3 H 5 ) 2 Cl 2 {1,3-{Ph 2 PC (O)} 2 (C 6 H 4 )}] (119) as depicted in Scheme 33. On the other hand, the reaction of ligand 20a with [Pd(COD)Cl 2 ] in the presence of AgClO 4 resulted in the formation of a PCP-type pincer complex, [PdCl{2,6-{Ph 2 PC(O)} 2 (C 6 H 3 )}] (120) via C-H bond activation in good yield.…”
Section: Group 7 Metal Chemistry (M = W)mentioning
confidence: 99%
“…Further, the synthesis of acyl phosphines 20a, 20c, and 21 via condensation of acid chlorides and diphenylphosphine even in the absence of base was achieved successfully as shown in Scheme 4. [30]3 -phosphanorbornadienes are considered as a potential source of metastable singlet phosphinidenes, which can further be utilized for the preparation of various phosphorus compounds. [31] It was initially observed that the 7λ 3 -phosphanobornadiene can be used only when lone pair of phosphorus is protected.…”
Section: Syntheses Of Acyl Phosphinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several advances in homogeneous catalysis over previous decades have been driven by this fact. 4 , 5 For systematic ligand design various metrics are used in order to describe the electronic and steric properties of phosphine ligands, including the Tolman electronic parameter (TEP), 6 , 7 cone angle, and the buried volume. 8 These measures facilitate the understanding of structure activity relationships in catalysis and build the foundation to computer-aided catalyst design.…”
Section: Introductionmentioning
confidence: 99%
“…First described in 1985 [24], such systems remain relatively rare, though-with the exception of type E-all possible motifs have been realized, with P-metalla-(type A) and C-metalla-(type B) systems the most heavily studied. Recently, as part of an extended program investigating transition metal compounds featuring low-coordinate phosphacarbons with potential for conjugation [25][26][27][28], we have prepared and studied a range of ruthenaphosphaalkenyl complexes of the type [Ru{P=CH(SiMe2R)}Cl(CO)(PPh3)2] (R = Me 1a, Ph 1b, Tol 1c) [29,30]. These are prepared by hydroruthenation of phosphaalkynes R3SiC≡P, following from methodology developed initially by Hill and Jones for t BuC≡P and related systems [31][32][33], and superficially related to Nixon's independent reduction of [(Ph3P)2Pt(η 2 -P≡C t Bu)] with Schwartz's reagent [34].…”
Section: Introductionmentioning
confidence: 99%